2021
DOI: 10.21203/rs.3.rs-281771/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Local Epidemiology of Methicillin-Resistant Staphylococcus aureus by Pulsed-Field Gel Electrophoresis in an Indian Tertiary Care Centre

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of community and hospital-acquired infections (HAIs). In the year preceding this study, our laboratory reported an MRSA isolation rate of 2% from 50,549 specimens. Molecular typing of MRSA identifies sources of infection, transmission chains and informs infection control practices, and pulsed-field gel electrophoresis (PFGE) is the gold standard. This study was conducted to gain an understanding of the local molecular epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The S. aureus forms no spores, however, may result in contaminating the food products throughout the processing and preparation of the food (6) . It is capable of https://www.indjst.org/ growing in many different temperature values (7 -48.5 o C; optimal 30-37 o C), pH (4.2 -9.3; optimal 7-7.5), and concentration of the NaCl up to 15%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The S. aureus forms no spores, however, may result in contaminating the food products throughout the processing and preparation of the food (6) . It is capable of https://www.indjst.org/ growing in many different temperature values (7 -48.5 o C; optimal 30-37 o C), pH (4.2 -9.3; optimal 7-7.5), and concentration of the NaCl up to 15%.…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of the S. aureus in the food products may take place from environment throughout the processing and handling (13) . Incorrect practices of the food handling in retail food industries have been considered to be contributing to high numbers of the outbreaks of the (1,6) . The researchers showed that most outbreaks of the FBD are a result of those practices (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation